Amblyraja doellojuradoi, Southern Thorny Skate - Pollom, R.; Dulvy, N. K.; Acuña, E.; Bustamante, C.; Chiaramonte, Gustavo Enrique; Cuevas, J. M.; Herman, K.; Paesch, L.; Pompert, J.; Velez Zuazo, X.
The Southern Thorny Skate (Amblyraja doellojuradoi) is a small (to 69 cm total length) deepwater skate that occurs in the Southeast Atlantic Ocean from Uruguay to Southern Argentina and the Burdwood Bank, including the Falkland Islands (Malvinas). It is demersal on the mid- and outer continental shelf and upper slope at depths of 50?1,000 m. This skate is captured as bycatch in demersal trawl fisheries and possibly on longlines targeting hake, squid, and Patagonian Toothfish (Dissostichus eleginoides), and is increasingly retained for human consumption. It has some refuge at depth and is not suspected to be undergoing a reduction in population size at this time. Therefore, the Southern Thorny Skate is assessed as Least Concern. Fil: Pollom, R. University Fraser Simon; Canadá Fil: Dulvy, N. K. University Fraser Simon; Canadá Fil: Acuña, E. Universidad Católica del Norte; Chile Fil: Bustamante, C. Universidad de Antofagasta; Chile Fil: Chiaramonte, Gustavo Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia". Estación Hidrobiológica de Puerto Quequén (sede Quequén); Argentina Fil: Cuevas, J. M. Wildlife Conservation Society; Estados Unidos Fil: Herman, K. Georgia Aquarium; Estados Unidos Fil: Paesch, L. Direccion Nacional de Recursos Acuaticos Uruguay Fil: Pompert, J. No especifíca; Fil: Velez Zuazo, X. No especifíca;